The nucleus accumbens in reward and aversion processing: insights and implications - Xu, Ying; Lin, Yingjie; Yu, Ming; Zhou, Kuikui (Frontiers in Behavioral Neuroscience, 2024)
The nucleus accumbens (NAc), a central component of the brain's reward circuitry, has been implicated in a wide range of behaviors and emotional states. Emerging evidence, primarily drawing from recent rodent studies, suggests that the function of the NAc in reward and aversion processing is multifaceted. Prolonged stress or drug use induces maladaptive neuronal function in the NAc circuitry, which results in pathological conditions. This review aims to provide comprehensive and up-to-date insights on the role of the NAc in motivated behavior regulation and highlights areas that demand further in-depth analysis. It synthesizes the latest findings on how distinct NAc neuronal populations and pathways contribute to the processing of opposite valences. The review examines how a range of neuromodulators, especially monoamines, influence the NAc's control over various motivational states. Furthermore, it delves into the complex underlying mechanisms of psychiatric disorders such as addiction and depression and evaluates prospective interventions to restore NAc functionality.